Multiple Functions of the Dmrt Genes in the Development of the Central Nervous System - Kikkawa, Takako; Osumi, Noriko (Frontiers in Neuroscience, 2021)
The Dmrt genes encode the transcription factor containing the DM (doublesex and mab-3) domain, an intertwined zinc finger-like DNA binding module. While Dmrt genes are mainly involved in the sexual development of various species, recent studies have revealed that Dmrt genes, which belong to the DmrtA subfamily, are differentially expressed in the embryonic brain and spinal cord and are essential for the development of the central nervous system. Herein, we summarize recent studies that reveal the multiple functions of the Dmrt genes in various aspects of vertebrate neural development, including brain patterning, neurogenesis, and the specification of neurons.